Protozoal coinfection in horses with equine protozoal myeloencephalitis in the eastern United States. (10th April 2018) - Schale, Sarah; Howe, Daniel; Yeargan, Michelle; Morrow, Jennifer K.; Graves, Amy; Johnson, Amy L.
Abstract : Background: Infection by 2 or more protozoa is linked with increased severity of disease in marine mammals with protozoan encephalitis. Hypothesis/Objectives: To assess whether horses with equine protozoal myeloencephalitis (EPM) caused by Sarcocystis neurona also have evidence of infection with Neospora hughesi or Toxoplasma gondii . We hypothesized that horses with EPM would be more likely than horses with cervical vertebral stenotic myelopathy (CVSM) to be positive for antibodies to multiple protozoan parasites. Animals: One hundred one horses with neurologic disease: 49 with EPM and 52 with CVSM. Methods: Case review. Archived serum and cerebrospinal fluid (CSF) from 101 horses were examined. Inclusion criteria included neurologic disease, antemortem or postmortem diagnosis of EPM or CVSM, and availability of serological results or archived samples for testing. Additional testing for antibodies was performed on serum for T. gondii, as well as serum and CSF for N. hughesi . Results: Horses with EPM were more likely than horses with CVSM to have positive immunologic results for S. neurona on serum (95.9% versus 76.9%, P = .0058), CSF (98.0% versus 44.2%, P < .00001), and serum : CSF titer ratio (91.8% versus 0%, P < .00001). Positive results for Neospora and Toxoplasma were uncommon, with total seroprevalence rates of 12.9% and 14.9%, respectively. The proportions of EPM cases testing positive for Neospora and Toxoplasma (16% and 12%) were not different from the proportions of CVSM cases testing positive (10% and 17%, P = .31 and .47, respectively). Conclusion: Results do not indicate an important role for protozoal coinfection in EPM in the eastern United States.